Fizicheskoe vospitanie uchashchikhsya obshcheobrazovatel'noi shkoly: sostoyanie, perspektivy i puti reorganizatsiyi - Lyakh, V. I.; Kopylov, Yu. A.; Malykhina, M. V.; Protchenko, T. A.; Polyanskaya, N. V. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
This theoretical study was hold to elaborate the problem of the personal physical culture in a pupil of a general education school. The authors of this paper consider that the structure of a pupil`s personal physical culture consists of six blocks, which are explained.